1990
DOI: 10.3109/00498259009046864
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity and toxicokinetics of chlorinated diphenyl ethers in trout

Abstract: 1. The LC50 and the uptake and elimination kinetics of 4-chlorodiphenyl ether (4-CDE), 2,4-dichlorodiphenyl ether (2,4-diCDE), 2,4,4'-trichlorodiphenyl ether (2,4,4'-triCDE) and 2,4,5,4'-tetrachlorodiphenyl ether (2,4,5,4'-tetraCDE) were examined in brook trout (Salvelinus fontinalis). The chlorinated diphenyl ethers (CDE) were administered in the water. 2. The 96 h LC50 of 4-CDE and 2,4-diCDE were 0.73 and 0.66 mg/l, respectively. The LC50 of 2,4,4'-triCDE and 2,4,5,4'-tetraCDE could not be determined since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The acute toxicity of these PCDEs to trout occurred at about 1 mg/L [22]. In rats, 2,2Ј,4,4Ј-tetrachlorinated diphenyl ether (PCDE 47), 2,2Ј,4,4Ј,5,5Ј-hexachlorinated diphenyl ether (PCDE 153), and 2,2Ј,3,4,4Ј,6,6Ј-heptachlorinated diphenyl ether (PCDE 184) caused increased liver weights at 500 mg/kg [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acute toxicity of these PCDEs to trout occurred at about 1 mg/L [22]. In rats, 2,2Ј,4,4Ј-tetrachlorinated diphenyl ether (PCDE 47), 2,2Ј,4,4Ј,5,5Ј-hexachlorinated diphenyl ether (PCDE 153), and 2,2Ј,3,4,4Ј,6,6Ј-heptachlorinated diphenyl ether (PCDE 184) caused increased liver weights at 500 mg/kg [23].…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of a small number of PCDEs has been studied in trout and rat [22,23]. The acute toxicity of these PCDEs to trout occurred at about 1 mg/L [22].…”
Section: Introductionmentioning
confidence: 99%
“…Radioactivity was found in all rat tissue examined with the greatest concentration in adipose tissue > skin > liver > kidney > muscle. 24 Chu et al 28 ' 29 also investigated the uptake and distribution of PCDE congeners in the rat. The results, which are consistent with those of Newsome et al, 21 showed that level of PCDEs deposited in liver and adipose tissue were dose dependent with adipose tissue having ten times the PCDE accumulation when compared to liver.…”
Section: Uptake Distribution and Excretion Of Pcdesmentioning
confidence: 98%
“…The PCDEs are rapidly taken up by trout, whereas their rate of elimination is slow and is related to their lipophilicity and biotransformation rates. 24 As noted for the PCBs, food and environmental samples will retain PCDE residues long after initial exposure. 27 The results of distribution and excretion studies conducted by Newsome et al 21 also indicated that the higher chlorinated PCDEs were expected to show an accumulation and tissue distribution pattern similar to that reported for PCBs.…”
Section: Uptake Distribution and Excretion Of Pcdesmentioning
confidence: 98%
See 1 more Smart Citation